GIS-based Historical and Cultural Value Sorting and Spatial Construction: Taking Taihu Lake Basin as an Example - Liu, Zuyue; Wang, Yan (International Planning History Society Proceedings, 2024)
The Taihu Lake Basin is rich in historical and cultural resources, its water network pattern and settlement texture showing the historical and cultural changes of urban and rural units. This paper takes the Taihu Lake Basin as the research object, excavates historical and cultural resources, and classifies their value elements and carriers. With GIS, we identify the main natural ecological patches, cultural value points and cultural routes to form a historical and cultural spatial system based on nature and humanities, then establish a systematic global historical and cultural spatial database. Firstly, we translate the geographic data of Taihu Lake Basin through ancient texts and ancient maps, locate the elements and carriers of cultural value on the historical and cultural spatial base map, and present the formation mechanism and value connotation in the form of spatial information, so as to facilitate more intuitive knowledge and understanding of the cultural distribution and evolution law in different periods, and provide historical thinking and future development suggestions for the historical and cultural spatial construction of Taihu Lake Basin.